2004
DOI: 10.1007/s00726-003-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taurine in glucose and taurine administration

Abstract: Taurine has several biological processes such as hypoglycemic action, antioxidation, detoxification, etc. To assess the effect of taurine administration on the guinea pigs with hyperglycemia, blood glucose, C-peptide levels together with morphologic alterations in the pancreatic ultrastructure were investigated in terms of hypoglycemic action and malondialdehyde and total sulfhydryl group levels with regard to oxidation-antioxidation relation. Animals were divided into four groups of six. Glucose supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…2B). This effect of taurine treatment is in agreement with some rodent studies that showed taurine administration attenuated the increase of blood glucose concentration during glucose tolerance testing [11][12][13][14][15][16][17] . In general, most glucose (>80%) is taken up by skeletal muscle 21) .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…2B). This effect of taurine treatment is in agreement with some rodent studies that showed taurine administration attenuated the increase of blood glucose concentration during glucose tolerance testing [11][12][13][14][15][16][17] . In general, most glucose (>80%) is taken up by skeletal muscle 21) .…”
Section: Discussionsupporting
confidence: 90%
“…Glycogen repletion in skeletal muscle after exercise is one of the major determinants of performance during subsequent exercise since higher pre-exercise glycogen content in skeletal muscle resulted in improving performance during both prolonged endurance and high-intensity intermittent exercise [2][3][4][5] . Some rodent studies have shown the possibility that taurine administration enhances glucose uptake in tissues [11][12][13][14][15][16][17] , which is one of the limiting factors for glycogen synthesis in skeletal muscle. Therefore, we hypothesized that taurine administration enhanced postexercise glycogen repletion in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, glycogen repletion in skeletal muscle after exercise should be a determinant for performance in subsequent exercise. Some rodent studies have reported that taurine administration enhances glucose uptake, which is a rate-limiting step for skeletal muscle glycogen re-synthesis [46][47][48][49][50][51] . Kulakowski et al showed that taurine administration increased incorporation of [ 3 H] deoxyglucose into skeletal muscle at the resting state in rats compared to a control group administered glucose only 46) .…”
Section: Effects Of Taurine Administration On Post-exercise Recoverymentioning
confidence: 99%